2020
DOI: 10.31100/histogram.v4i1.569
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Literasi Matematika Siswa Pada Konten Space and Shape

Abstract: Kemampuan literasi matematika masih menjadi tren di dunia pendidikan saat ini. PISA merupakan salah satu studi yang mengukur kemampuan siswa dalam proses penalaran, memberikan argumen dan pemecahan masalah. Dari beberapa konten yang diukur, peneliti memfokuskan pada space and shape materi pythagoras. Pertanyaan pada penelitian ini adalah bagiamana kemampuan literasi siswa pada konten space and shape materi pythagoras. Pada penelitian ini, peneliti menggunakan pendekatan kualitatif dengan metode observasi, doku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…The representation ability is the ability to represent mathematical objects such as graphs, tables, diagrams, pictures, equations, formulas, and other concrete forms. This result is in line with research conducted by Munfarikhatin, Natsir, and Merauke (2020), stating that some students have not been able to use their mathematical skills to solve PISA mathematics problems related to change and relationship contents. Meanwhile, Hasibuan, Fauzi, and Mukhtar (2019) stated that students' mathematical literacy skills in change and relationship contents are generally above average and classified as quite good.…”
Section: Figure 4 Cubesupporting
confidence: 91%
“…The representation ability is the ability to represent mathematical objects such as graphs, tables, diagrams, pictures, equations, formulas, and other concrete forms. This result is in line with research conducted by Munfarikhatin, Natsir, and Merauke (2020), stating that some students have not been able to use their mathematical skills to solve PISA mathematics problems related to change and relationship contents. Meanwhile, Hasibuan, Fauzi, and Mukhtar (2019) stated that students' mathematical literacy skills in change and relationship contents are generally above average and classified as quite good.…”
Section: Figure 4 Cubesupporting
confidence: 91%
“…Research on junior high school students was carried out on 8th grade students, there were 6 research articles and 9th grade students two research articles. 1) Research on 8th graders was conducted at SMP N 1 Winong, Pati, Central Java (Munfarikhatin & Natsir, 2020) which showed that students' literacy skills on space shape content were still very low; 2) Research on 8th grade students at SMP Negeri 2 Wonopringgo, Pekalongan, Central Java (Khaerunisak et al, 2017)…”
Section: ) Research On Mathematical Literacy Analysis At the Junior H...mentioning
confidence: 99%
“…Hal ini berarti siswa belum mampu menggunakan operasi matematika dengan benar, serta belum mampu menggunakan keterampilan matematikanya untuk menyelesaikan soal matematika yang paling mudah (OECD, 2013). Siswa berkemampuan rendah hanya mampu menempati level 3, siswa berkemampuan sedang dan siswa berkemampuan tinggi menempati level 4 yang disebabkan karena siswa tidak terbiasa dengan soal-soal dalam konteks kehidupan sehari-hari yang kompleks yang memerlukan penalaran logis (Munfarikhatin & Natsir, 2013).…”
Section: Pendahuluanunclassified